A Note on Ivan Illich - Polić-Bobić, Mirjana (Array, 2011)
Theologian Ivan Illich has been known as a dissident from the official policy of the Catholic church ever since 2nd Vatican council. In this paper his attitude has been analysed from the optics of his activity in Latin America, namely Mexico, and his opposition to the programme USAid designed for its voulntaires in that area.